Chronic hepatitis C virus infections: predictive value of genotype and level of viraemia on disease progression and response to interferon alpha. Issue 3 (March 1995) - Booth, J C; Foster, G R; Kumar, U; Galassini, R; Goldin, R D; Brown, J L; Thomas, H C
Abstract : The effects of hepatitis C virus genotype and viraemia on disease outcome in patients with chronic hepatitis C virus infection were studied. Patients infected with genotype 1 tended to develop more severe disease, and to respond less well to interferon (IFN) treatment, but no pretreatment variable successfully predicted either the severity of the disease or the response to IFN. Failure to eliminate the virus during the first three months of therapy, however, predicted a failure to derive long term benefit from the current IFN regime. Hence pretreatment variables cannot be used to determine whether individual patients will respond to IFN, but observations during the first three months of therapy can be used to decide which patients will not respond to prolonged therapy. In these patients consideration should be given to changing the IFN dosing regime or using alternative treatments.